As dificuldades para implantação do gerenciamento de processos de negócio em uma instituição federal de educação tecnológica - Santos, Osmario Pereira dos (Universidade Federal de São Carlos, 2021)
With effort to face great challenges of public management modernization in Brazil, whose embryo were the experiences verified in the United States and England, which became known as the New Public Management, Decree 5,378 of February 23, 2005 has etablished the Public Management National Program and Debureaucratization – GESPÚBLICA. Its main banner was searching for excellence in management keeping the public services characteristics. Since then, Brazilian public administration could be noticed, not only in direct administration bodies, but also in those of indirect administration, great interest in new management techniques and tools, with more managerial bias which in a recente past were considered private sector´s exclusive domain. Such as Business Process Management practices. However, the implementation of process management practices in a public organization is not a trivial task. It implies, above all, the breaking of old paradigms consolidated over decades and, somehow, they still define how work must be performed in the public sector. Such changes can bring a very high degree of complexity to its implementation, creating sometimes insurmountable difficulties, requiring great abilities on part of those responsible for its implementation. Therefore, the general aim of this research was to detect the difficulties in implementing the management of business process in a Federal Technological Education Institution, aiming to overcome them. The methodology adopted followed the taxonomy suggested by Vergara (2016), which uses two basic criteria for researches classification: in terms of ends and in terms of means. As to the ends, it can be understood as decriptive and exploratory; as to the means, this is a case study performed from Process Mapping Commission of the Academic Records Coordination of a Federal Institute of Education, Science and Technology. Data collection was accomplished from a combination of the following techniques: documentary analysis (ordinance, resolutions, Institutional Development Plan – PDI, management report); details are available on the Institution´s website; and the application of a semi-structured online questionnaire. The sample population was based on a non-probabilistic sample which considerated the access facility to the research subjects (Vergara, 2016). Therfore, twenty professionals were selected, including members and former members of the Process Mapping Comittee, to whom the link to access the quetionnaire was sent by email. A total of fifteen questionnaires were completed. The research results supported the difficulties pointed out by the specialized literature that served as theoretical foundation for this research and indicated the gaps that must be filled if the Intitution present insterest in overcoming such difficulties. Based on this, as a final recomendation, the adoption of process management practices, pointed out by the consulted authors, was suggested, aiming the consolidation of the implementation project of the Business Process Management in the Institution.
The difficulties for implementing the management of business processes in a federal institution of technological education
Keywords: Administração pública; Ciclo de vida de BPM; Gestão de processos de negócio; Instituições federais de ensino superior; Melhoria contínua; Public administration; BPM lifecycle; Business processes management; Federal institutions of higher education; Continuous improvement; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS